TOXIC ALCOHOL POISONING: A CASE REPORT - SANAL K THOMAS; ATHULYA G ASOKAN; AJEESH KOSHY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
During the COVID-19 pandemic, toxic alcohol poisoning, notably from methanol, has emerged as a significant concern due to increased consumption of illicit liquor amidst lockdown restrictions. We present a case of a middle-aged man who developed altered consciousness, metabolic acidosis, and shock two days after ingesting hospital spirit. Although initial qualitative tests only detected ethanol, subsequent MRI findings showed classical signs of methanol poisoning, including basal ganglia abnormalities. Prompt management with dialysis, ventilatory support, and adjunctive therapy successfully addressed the acute phase despite the patient remaining delirious for seven days. This case underscores the importance of considering methanol toxicity even in the absence of direct evidence, necessitating comprehensive diagnostic approaches. Awareness and incorporating point-of-care assessments such as arterial blood gas analysis and osmolar gap evaluation in suspected cases are crucial, especially in resource-limited settings. Recognizing unexplained high anion gap metabolic acidosis with a high osmolar gap and characteristic MRI findings can aid in the early diagnosis and management of toxic alcohol poisoning